A comprehensive ethnic-based analysis of alpha thalassaemia allelle frequency in northern Thailand article - Kulaphisit M. (2017)
© 2017 The Author(s). Alpha (α)-thalassaemia is one of the most prevalent hereditary blood disorders, commonly affecting Southeast Asian people, with the highest incidence (30-40%) being seen in northern Thailand. However, this high incidence was estimated without consideration of the variations between ethnic populations and the geographical location of the populations. To address this issue, a total of 688 samples from 13 different northern Thai ethnic groups (30 villages) categorized into three linguistic groups were genotyped for deletional alpha-thalass aemia (-α 3.7 ,-α 4.2 ,- SEA and- THAI ) and/or non-deletional alpha-thalassaemiaα CS and α PS ) via multiplex gap-PCR and dot-blot hybridization, respectively. Alpha + (-α 3.7 ,-α 4.2 , α CS and α PS ) and alpha°-thalassaemia (- SEA and- THAI ) allele frequencies (with 95% Confidence Interval) were the highest in the Sino-Tibetan group [0.13 (0.08-0.18)] and the Tai-Kadai group [0.03 (0.02-0.05)] , respectively. With regards to ethnicity, the varying allele frequency of α + and α°-thalassaemia amongst a variety of ethnicgroups was observed. The highest α + -thalassaemia allele frequency wasfound in the Paluang [0.21 (0.10-0.37)] while α°-thalassaemia allele frequency was the highest in the Yuan [0.04 (0.01-0.10)] . These detailed results of alpha thalassaemia allele frequency and genetic diversity amongst the northern Thai ethnic groups demonstrate the need for ethnicity based thalassaemia prevention programs.